LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR (Kn) IN CIRRHINA MRIGALA (HAM.) FROM LAMADA FISH FARM CENTER, AGRA - RANI, RITA; GAUR, K. K.; TIWARI, VISHAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
The present investigation has been made with a view to study the length-weight relationship and condition factor in Cirrhina mrigala (Ham), which are correlated with growth, management and marketing of the fish population. Total 49 specimens of C. mrigala were studied during the last two years of study period. The departure from cubic law has been tested and correlation coefficient r and Kn value (condition factor) have also been computed. The study revealed that there was a close relationship between length and weight, and is a very important aspect of fish biological investigation.